Effect of Red, Blue, Green LEDs on the Germination and Seedling Growth of Rice - Hoque, MN; Islam, MZ; Rahman, M; Biswas, B; Mahmud, N (Journal of Environmental Science and Natural Resources, 2022)
The present investigations attempted to study the effects of red, blue and green LEDs effect on seed germination, first leaf length, first leaf blade length, root length, seedling fresh and dry weight. Seeds of five rice varieties were germinated and seedlings were grown under dark and red, blue, green LEDs lighting system (6 h photoperiod and 18 h dark) set at 20 to 24± 2 °C for day and night respectively and 70 ± 2 % relative humidity in a control chamber for 14 days (starting 3 days after plated for germination). The result showed that germination percent increased significantly in BRRIdhan52 and BRRIdhan75 under red-blue-green LEDs than dark. First leaf length increased in dark than LEDs treatment. Longest leaf (10.42 cm) was recorded in BRRIdhan86 in dark and under LEDs in BRRIdhan75 (5.70 cm). First leaf blade length was highest in BRRIdhan52 (2.56 cm) under LEDs treatment and in dark BRRIdhan67 had the longest (2.48 cm). Root length was also increased significantly in studied rice varieties. Though, longest root was found in dark in BRRIdhan71 (6.69 cm) and under LEDs, BRRIdhan71 had the longest root (6.35 cm). Seedling fresh and dry weight were highest under red-blue-dark LEDs treatment. BRRIdhan86 had the highest and BRRIdhan67 had the lowest seedling fresh and dry weight with a range of 0.323g to 0.451g and 0.037g to 0.052g respectively than dark condition. Root length showed positive significant correlation with seedling fresh weight (r = 0.876) and seedling dry weight (r = 0.873). Whereas seedling fresh weight showed complete correlation (r = 1) with seedling dry weight. Response index was negative for first leaf length in the studied rice varieties. Highest response index (35.93) was observed for seedling fresh and dry weight in BRRIdhan75 and BRRIdhan86. Environ. Sci. & Natural Resources, 13(1&2): 63-69, 2020